A flight to the future with a glimpse into the past: A Águia – an anti avant-garde Portuguese experience? - Samyn, Henrique Marques (Revista de Letras, 2010)
The Portuguese literary magazine A Águia was founded in 1910 by the journalist Álvaro Pinto, with the goal of promoting the rebirth of a culture seen as decadent at the beginning of the twentieth century. From 1911 to 1922, under the infl uence of Teixeira de Pascoaes, A Águia was dedicated to the dissemination of “Saudosismo”, the nationalistic movement created by him. Although severa lvanguardist movements took place in Portugal at this time, A Águia didn’t participatein any of them. The aim of this article is to investigate why this happened, and in what sense it is possible to qualify A Águia as an “anti avant-garde” magazine. Keywords: A Águia (1st and 2nd series). Vanguardism. Saudosismo. Portuguese Literature.